Analisis Rentabilitas Kopi Bubuk Cap Dua Putra di Kecamatan Selupu Rejang Kabupaten Rejang Lebong - Ningrum Ningrum; Gracia Gabrienda; Putri Milanda Bainamus (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2024)
In the Rejang Lebong Regency area, one of the areas in Selupu Rejang District is that there is a Ground Coffee business called Cap Dua Putra which makes processed robusta coffee into ground coffee. The Cap Dua Putra ground coffee processing business has been running for more than twelve years. With the criteria of length of business and the number of competitors in the coffee processing industry. Researchers are interested in looking at business feasibility through a profitability approach, which is a comparison between profit and capital. This research aims to determine the profitability and profit value of Cap Dua Putra ground coffee. The data used in the research are primary and secondary data, namely annual data on ground coffee production in 2022. This data comes from field questionnaires. This research was carried out at the Cap Dua Putra Ground Coffee business, the research period was from April to completion. The sampling technique is non-probability sampling, with the criteria being a business that has been established for more than twelve years. Results and research show that the production costs incurred in the Cap Dua Putra ground coffee business are IDR. 163,235,000,-/year. The production value of this business is IDR. 228,000,000/year with production of 4200 kg/year. The selling price is Rp. 60,000,-/kg. the profit obtained is Rp. 63,407,000,-/year. The profitability value from the comparison of profit and capital is 38.84 percent. This means that the business makes profits that are much greater than the prevailing interest rates.